Sviluppo dell'intelligenza corporeo-cinestetica nel gestire e canalizzare le paure in età prescolare - Manuela Valentini; Valentina Nicolini (Pensa MultiMedia, 2021)
The purpose of this experimental investigation was to examine whether the promotion in the school environment of a motor activity aimed at developing each child's kinesthetic intelligence could result in an improvement in the management and channeling of their fears. Through search engines such as Google Scholar and EBSCO, eight studies that investigated the positive influence of gross/fine motor activity on the emotional sphere of the child were selected. The research was carried out using some key words: "physical activity", "physical education", "psychomotricity", "children", "kinesthetic intelligence", "fear in preschool children". The experimentation was conducted in a primary school in Rimini, with 4- and 5-years old children (except for a 3-years old girl); it started in December 2019 and was due to end in June 2020. A working group and a control group were identified, and two pre-tests were given to both: TGM (Gross Motor Skills Assessment Test) and KFQ (Koala Fear Questionnaire). Motor activities that would fully involve the pupils' bodies and stimulate their kinesthetic intelligence to address the issue of fear were proposed to the workgroup. Due to the Covid-19 pandemic, the experimentation had to be stopped in February 2020. Despite the impossibility of continuing in presence, also thanks to the collaboration of parents and teachers, a new twist was given to the educational research.